2021
DOI: 10.1038/s41537-021-00143-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA hydrolysing IgG catalytic antibodies: an emerging link between psychoses and autoimmunity

Abstract: It is not uncommon to observe autoimmune comorbidities in a significant subset of patients with psychotic disorders, namely schizophrenia (SCZ) and bipolar disorder (BPD). To understand the autoimmune basis, the DNA abyzme activity mediated by serum polyclonal IgG Abs were examined in psychoses patients, quantitatively, by an in-house optimized DNase assay. A similar activity exhibited by IgG Abs from neuropsychiatric-systemic lupus erythematosus (NP-SLE) patients was used as a comparator. Our data revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
4
0
1
Order By: Relevance
“…A comparison of the level of MBP-hydrolyzing activity in autoimmune and mental disorders showed that the percentage of antibodies with pronounced activity decreases in the following series: MS (84%) < schizophrenia (69%) < BAR (52%) [34,37]. Our results are consistent with the first study of DNA-hydrolyzing IgG in bipolar disorder, which showed a decrease in activity levels compared with patients with schizophrenia and SLE [43]. The differences in the level of proteolytic activity of serum antibodies revealed in this article indirectly indicate differences in the pathogenesis of affective and psychotic disorders, when autoimmunity can be much less pronounced in bipolar disorder than in schizophrenia.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A comparison of the level of MBP-hydrolyzing activity in autoimmune and mental disorders showed that the percentage of antibodies with pronounced activity decreases in the following series: MS (84%) < schizophrenia (69%) < BAR (52%) [34,37]. Our results are consistent with the first study of DNA-hydrolyzing IgG in bipolar disorder, which showed a decrease in activity levels compared with patients with schizophrenia and SLE [43]. The differences in the level of proteolytic activity of serum antibodies revealed in this article indirectly indicate differences in the pathogenesis of affective and psychotic disorders, when autoimmunity can be much less pronounced in bipolar disorder than in schizophrenia.…”
Section: Discussionsupporting
confidence: 89%
“…However, these results are consistent with data on DNA-binding and DNA-hydrolyzing IgGs in BD. Ramesh R. et al showed that the DNA-hydrolyzing activity of antibodies is increased in patients with bipolar disorder compared to healthy individuals, but the titers of antibodies to DNA are even lower than in healthy subjects [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among antigen-binding antibodies there are antibodies that can catalytically modify the antigen. Such antibodies have been identified in various mental disorders [ 25 , 26 ]. In patients with schizophrenia, catalytic antibodies (abzymes) hydrolyzing DNA [ 27 ], RNA, and miRNA [ 28 ], histones [ 29 ], and myelin basic protein (MBP) [ 20 , 30 ] have been previously found.…”
Section: Introductionmentioning
confidence: 99%
“…В последние годы в сыворотке крови пациентов, страдающих шизофренией, обнаружены антитела, обладающие каталитическими свойствами (абзимы). К настоящему времени выявлены следующие абзимы: ДНК, РНК, ОБМ и гистон-гидролизующие и расщепляющие гидроперекись водорода иммуноглобулины класса G (IgG) [7,8,9]. Вместе с тем биологическая роль абзимов в патогенезе заболевания не изучена всесторонне и не установлена окончательно.…”
unclassified